KEANEKARAGAMAN JENIS TUMBUHAN PAKU-PAKUAN (Pteridophyta) DI DESA BEMBAN KAWASAN HUTAN LINDUNG GUNUNG AMBAWANG KECAMATAN KUBU KABUPATEN KUBU RAYA - Yuliastuti, Erni; Herawatiningsih, Ratna; dina, Wah (Universitas Tanjungpura, 2014)
Research on Fern Diversity (Pteridophyta) In Bemban village In Mount Ambawang Protected Forest Kubu Kubu Raya District of West Kalimantan Province was held on September 16 th to October 7 th , 2013. Sampling plot was taken purposive where there were many fern found. There were four sampling plot based on height. Plot I located in 50-150 m above sea level altitude, plot II in 150-250 m above sea level altitude, plot III in 250-350 m above sea level altitude,and plot IV in 50-150 m above sea level altitude (rubber plantations). Each sampling plot 40 m x 40 m, divided into 160 subplot 2 m x 5 m aech. There were 13 fern species with 4162 individual these species consist of 8 terresterial fern with 3799 individual, and 5 epiphytic fern with 813 individuals. The plot at altitude of 50-150 m,were dominated by Lygodium circinatum and Asplenium nidus, altitude 150-250 m were dominated by Acrostichum spesiocum and Asplenium nidus, altitude 250-350 m dominated by Selaginella wildenowii, Asplenium longisimmum height of 50-150 m asl (rubber plantation) dominated by Nephrolepis biserrata and Asplenium nidus. The highest diversity index value was at altitude 150-250 m (2,043) which means the species diversity of ferns were low. Similarity index was highest between altitude 250-350 m and altitde 50-150 m in rubber plantation,in the value 5,638 %. It means between thw different plot there is no similarity (≤ 25 %). Keywords: Ferns, biodiversity, forest protected mount Ambawa